Heart histological changes in rats log-term exposed to organophosphate - Calore, Edenilson Eduardo (2006)
Organophosphate can be responsible for causing acute intoxications, and in inducing delayed effects. Effects on the cardio-vascular system after long-term exposition to organophosphate have not been described, so far. The objective of the present study was to study whether these effects on heart could be caused by these compounds contact. Adult male Wistar albino rats, divided into groups, received weekly an enteral sub-lethal dose of organophosphate methamidophos for 12 consecutive weeks. Then, their hearts were examined by means of histological and morphometric methods. Hipertrophy of cardiac muscle cells in treated animals was observed, and this finding was confirmed by means of morphometric methods, that is, the measurement of smallest diameter of cardiac muscular cells. The mean value of the smallest diameter of cardiac myocytes from controls was 64.93 + 5.82μm, and from two treated animals groups was 82.24+12.39μm and 88.88 + 10.19 μm, respectively. Although the functional consequences of cardiac hypertrophy were not the object of the present study, the 3 month-treated animals did not show any sign of heart failure. However, it could not be disregarded that long term exposition to organophosphate might cause any functional cardiac disorder, including heart failure. These heart histology alterations are relevant, as Brazilian people are frequently undergo to long-term exposure to these compound with deleterious results.